Analisis Produksi Padi di Kota Tasikmalaya Tahun 2020–2025: Tantangan dan Strategi Menuju Swasembada Pangan Nasional - Dudung Dudung; Apdan Pebriana; Agus Hendar; Yaya Sunarya; D Yadi Heryadi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to analyze the dynamics of rice production in Tasikmalaya City during the period 2020 to 2025, as well as identify challenges and formulate relevant strategies in order to support national food self-sufficiency. The approach used is descriptive qualitative by utilizing secondary data from the Central Statistics Agency (BPS) and various policy documents and relevant scientific studies. The results of the study indicate that rice production in Tasikmalaya City experiences fluctuations influenced by natural factors, policies, and pressure on agricultural land. The main challenges faced include land conversion, limited technology, and farmer access to training and financing. To overcome this, the proposed strategy includes protecting agricultural land, increasing farmer capacity, and strengthening agricultural institutions and infrastructure. This study makes an important contribution to efforts to increase regional rice production in supporting national food security in a sustainable manner.